2017
DOI: 10.1159/000455906
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and In-Hospital Mortality after Coronary Artery Bypass Graft versus Percutaneous Coronary Intervention: A Nationwide Study

Abstract: Background: Post-procedural acute kidney injury (AKI) is associated with significantly increased short- and long-term mortalities, and renal loss. Few studies have compared the incidence of post-procedural AKI and in-hospital mortality between 2 major modalities of revascularization - coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) - and results have been inconsistent. Methods: We generated a propensity score-matched cohort that includes a total of 286,670 hospitalizations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Furthermore, we should pay attention to acute kidney injury, even though our research did not demonstrate any incidence of acute kidney injury. Shen et al [53] found that the incidence of AKI after CABG was higher than after PCI (8.9 vs. 4.5%; OR, 2.05; 95% CI, 1.99–2.12; p < 0.001), which reminded us to pay more attention to protecting the kidneys during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we should pay attention to acute kidney injury, even though our research did not demonstrate any incidence of acute kidney injury. Shen et al [53] found that the incidence of AKI after CABG was higher than after PCI (8.9 vs. 4.5%; OR, 2.05; 95% CI, 1.99–2.12; p < 0.001), which reminded us to pay more attention to protecting the kidneys during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with multiple comorbidities and those with advanced CKD are often excluded from clinical trials or cardiovascular interventional studies because of a higher risk of complications and adverse events, making retrospective studies the sole source of information. Large retrospective studies comparing AKI following CABG versus PCI reported 1.6-, 2.6-and 2fold higher risks of AKI after CABG compared with PCI [16,17], and a higher incidence of AKI in patients with CKD compared with patients with normal kidney function, with an incrementally higher frequency of AKI in patients with more advanced stages of CKD [16,17]. Contrasting these findings, another VA-based study [14] described a relatively higher incidence of AKI after cardiac surgery in patients with baseline eGFR >45 mL/min/1.73 m 2 compared with baseline eGFR <45 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…AKI is associated with high in-hospital and long-term mortality and with progression to ESRD [12][13][14][15]. The incidence of AKI has been found to be higher after CABG compared with PCI in patients with normal kidney function and with mild and moderate CKD [16,17]. However, the relative risk of AKI associated with CABG versus PCI in patients with advanced CKD (who may be more susceptible to radiocontrast-associated AKI) is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The AKI rate in our preliminary report is within this range but rather close to the upper limited reported by other authors. It must be noted that the incidence seems to be higher in prospective single-center analyses [ 11 13 ] than in retrospective cohort studies of large national databases [ 14 , 15 ]. In the latter it may be underestimated and underreported as it based predominantly on analyses of the medical records where AKI was identified using International Classification of Diseases, 9 th Revision diagnosis codes.…”
Section: Discussionmentioning
confidence: 99%